Assessing the relationship between blood transfusion products and non-Hodgkin’s lymphoma incidence: A longitudinal retrospective cohort study (2004-2022) - Abdulrahman M. Shadid; Naif Alsaber; Abdullah M. Shadid; Faris R. Al Mubarak; Mohaned Makkawi; Farjah H. Algahtani; May AlMoshary (Journal of Family Medicine and Primary Care)
Background: The association between blood product transfusion and developing non-Hodgkin’s lymphoma (NHL) risks remains debated. Previous studies have established a link between blood products and NHL risks among hospitalized patients. Therefore, this study aimed to evaluate the association between NHL risk and blood transfusion among recipients through a large cohort study with an 18-year follow-up. Methods: This retrospective cohort study included approximately 8,558 patients who received at least one blood transfusion from our institution’s medical records between 2004 and 2022. We extracted each blood transfusion record from the system database, excluding incomplete, cancelled, and discontinued cases. Patients with lymphoma from the hospital databases were followed up until the end of 2023. Those with a prior diagnosis of NHL or any other hematologic malignancy were excluded. Histopathological analysis of biopsy specimens confirmed the NHL diagnosis. Results: In this cohort study, we analyzed participants with a median age of 46, comprising 48.2% males and 51.8% females. The administered transfusion products included packed red blood cells (pRBCs), platelets, fresh frozen plasma (FFP), and cryoprecipitate. Notably, 2 out of 8,558 (0.023%) blood recipients developed NHL, compared to 6 out of 100,000 (0.006%) in the general Saudi population, indicating a significant association between NHL risk and blood transfusion (P < 0.001). However, our findings did not reveal a significant relationship between increased NHL incidence and individual blood products. Conclusion: This study revealed that blood transfusion recipients had a significantly higher incidence of NHL than the general population. However, no distinct association was found between the risk of developing NHL and any specific blood transfusion product. The findings suggest that the underlying diseases necessitating blood transfusion, rather than the transfusion products themselves, may be the primary cause of the increased risk. Further research is warranted, utilizing larger samples and prospective study designs and controlling for confounding factors to elucidate the underlying reasons for this association.